Seismic vulnerability assessment of old building aggregates - Maio, Rui André Simões Dias (2014)
The present dissertation approaches the assessment of the seismic vulnerability of old stone masonry building aggregates. With this topic it is presented a review on the most recent methods and tools used for the seismic vulnerability assessment of masonry buildings, focusing the research developed both in Italy and Portugal. Moreover, a case study of an old stone masonry building aggregate was assessed, which is located in San Pio delle Camere (Abruzzo, Italy), slightly a ected by the 6th April 2009 L'Aquila earthquake. This building aggregate was modelled using the STA DATA software 3muri®. On one hand, static non-linear numerical analysis was performed to obtain capacity curves and a prediction of the damage distribution in the structure, caused by the input seismic action (hybrid method), on the other hand indirect methods were used, based on di erent vulnerability index formulations.